ANALISIS FRASA ENDOSENTRIS DAN EKSOSENTRIS PADA LAGU LESUNG PIPI CIPTAAN RAIM LAODE - Putri Schatzi Abdillah; Aura Kirana Maharani; Irena Mulyana Syabilla; Nurul Camilah Rahdianti; Iis Lisnawati (Jurnal Bastra (Bahasa dan Sastra), 2025)
This study aims to identify and analyze endocentric and exocentric phrases contained in the lyrics of the song "Lesung Pipi" created by Raim Laode. Phrases as grammatical units consisting of two or more words that do not exceed the function limits of clause elements are an important aspect in the study of syntax. The research method used is a qualitative descriptive method with document analysis techniques. The results of the study show that in the lyrics of the song "Lesung Pipi" two types of phrases were found, namely endocentric phrases and exocentric phrases. The endocentric phrases found consist of nominal endocentric phrases, verbal endocentric phrases, adverbial endocentric phrases, and adjectival endocentric phrases. The distribution of endocentric phrases in the song lyrics is more dominant compared to exocentric phrases. This study provides an overview of the syntactic structure used in contemporary Indonesian popular songs and how the choice of phrase structure can affect the aesthetics and message delivery in a song.